2015
DOI: 10.3174/ajnr.a4439
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inner Ear Contrast Enhancement among Patients with Unilateral Inner Ear Symptoms in MR Images Obtained 10 Minutes and 4 Hours after Gadolinium Injection

Abstract: BACKGROUND AND PURPOSE:Recently 4-hour delayed-enhanced 3D-FLAIR MR imaging has been used in pathophysiologic analysis of the inner ear in many auditory diseases, including sudden sensorineural hearing loss, but comparison among different time points is not clear in patients with unilateral inner ear symptoms. We compared the signal-intensity ratios of the inner ears in patients with unilateral inner ear symptoms on 10-minute delayed-enhanced and 4-hour delayed-enhanced 3D-FLAIR MR images after IV gadolinium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 13 publications
2
28
1
1
Order By: Relevance
“…Visualization of the inflamed vestibular nerve has become possible because of increased imaging sensitivity due to the greater magnetic field strength of scanners, as well as developments in image sequence techniques such as 3D‐FLAIR . In addition, the application of high‐dose IV Gd has increased MR enhancement . These MR techniques have also enabled better visualization of inner ear structures .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visualization of the inflamed vestibular nerve has become possible because of increased imaging sensitivity due to the greater magnetic field strength of scanners, as well as developments in image sequence techniques such as 3D‐FLAIR . In addition, the application of high‐dose IV Gd has increased MR enhancement . These MR techniques have also enabled better visualization of inner ear structures .…”
Section: Discussionmentioning
confidence: 99%
“…Pathological processes in VN may induce hyperemia of the affected nerve and loosening of the BLB, followed by diffusion of Gd into the fluid space of the inner ear. Presumably, simple diffusion of Gd requires time; previous reports have suggested that the enhancement of inner ear structures is most intense 4 hours after IV Gd injection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of perilymphatic enhancement in 3-Tesla MRI also depend on the interval between the intravenous contrast administration and imaging. Research showed that a 4-hour delay results in greater contrast enhancement within the perilymph 28,29 . Jerin et al reported a case of a patient with VS and endolymphatic hydrops, in which ELH was revealed with the use of an inner ear LEIM MRI with an axial 3D Real-IR sequence; the authors recommended performing locally contrast-enhanced inner ear MRI in those cases in which an ELH is suspected 14 .…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish endolymph and perilymph by SSNHL Tagaya et al introduced 4‐hour delayed images of 3T FLAIR MRI with double doses (0.2 mmol/kg) of IV Gd. A recent investigation concluded that 4‐hour delayed images were more useful than 10‐minute delayed images for anatomic discrimination in unilateral inner ear diseases that cause neural inflammation …”
Section: Introductionmentioning
confidence: 99%